Quranic Concept of the Family System and West: Analytical Study - Abdul Manan Cheema; Hassan Akram (jihat-ul-islam, 2022)
The entire world has become global village because of advancement of technology. In modern times of globalization, Muslims are being alienated from their civilization, culture and a strong family system. It is clear that western family system is promoting in the Islamic societies. Modern generation of Muslim societies is imitating western culture. So, Muslim family system in on the path of misguidance in modern times. In the West, the family system has become unstable, while in the East, the foundations of the family system are being hollowed out. Islam is complete code of life and provides a strong basis of an ideal family system. Therefore, there is no justificaiton for imitation of western civilizaiton. Islam provides complete and comprehensive guidance in every aspect of life. It is need of time to educate new Muslim generation with basic elements of Islamic family system in the light of Islam teachings. This research work explores significance and Intellectual application of Islamic family system in Islamic societies in modern times.